A model for magnetic actuation of the artificial multicilia - (:unkn) unknown (My University, 2009)
The current paper continues the analysis of a completely novel method of fluid manipulation technology in microfluidics systems, inspired by nature, namely by the mechanisms found in ciliates. More information on this subject can be found at http://www.hitech-projects.com/euprojects/artic/. The paper presents a fast and accurate method to model the magnetic behavior of an artificial cilium. The method is based on Maxwell equations, formulated as integral equations for the magnetization. Also this paper consists on assessing magnetic actuation as a practical tool for obtaining a consistent one-directional fluid flow. The actuation mechanism consists of a bi-directional rotating excitation magnetic field. The magnetization induced by the magnetic field was calculated in a separate routine based on the Integral Nonlinear Equations Approach with ID discretization of wire (cilium). Time averaged x-coordinate mass flow rates are computed for several cilium configurations resulting.